AlPW12O40 and AlPMo12O40 as Highly Effective and Eco-friendly Catalysts for Aldoximation of Aldehydes Under Solvent-Free Conditions - FAZAELI, RAZIEH; ALIYAN, HAMID (Asian Journal of Chemistry, 2010)
The oxime formation of aromatic aldehydes has directly been carried out with hydroxylamine hydrochloride using heteropoly acids (AlPW12O40, AlPMo12O40) as catalysts in the absence of solvent. It is found that these heteropoly acids were effective catalysts for the formation of oxime of aldehydes. This method consistently has the advantage of high yields of the products, short reaction time, mild and solvent-free conditions, cleaner reactions and isolation procedures.